Potensi Pelanggaran Pengelolaan Limbah Bahan Berbahaya dan Beracun - Arif Jumari (BESTUUR, 2019)
AbstractThe increasing of the volum and kinds of Hazardous and Toxic Waste (B3) endangered the environment and life so it has been managed well. As a state law, of the Law No. 32/ 2009 of The Protection and Management of the Environment (Law of PPLH) and its derivatives, i.e, Government Regulation No. 101/2014 of the Management of Hazardous and Toxic Waste (B3) and The ministry Regulation No.P 95/2018 of integrated licency of Management of Hazardous and Toxic Waste (B3) with environment licence through the electronically integrated service of a company licence, should fulfill  The Law Theory of Law Substance, Law Structure and Law Culture. It also should be able to ensure the legal certainty, justice and expediency. The aims of the research were to analyze The Regulations of Management of Hazardous and Toxic Waste (B3) mentioned above and to describe the violation potential the related Regulations.The result of analysis showed that The Regulations had good law substance and law structure. The good implementation of the Regulations could be expected to bring up a good law culture.  The Regulations would be able give the legal certainty, justice and expediency when it was well implemented. The violation potential could be not only from the Law Subject in related to the licensing and supervision but also from the Law Object in related to the abuse of licence anda data manipulation. The violation can be minimized by the licence simplification,   the ease of data acces and the increasing of number and quality of supervision. The conclusion of research were that the Regulations related to Management of Hazardous and Toxic Waste (B3) were good of both Law Theory and Law function, but many violation potential to the regulations so it had to be anticipated. Keywords: Management of Hazardous and Toxic Waste, State, Law Function, Violation potential.